Fiscal multipliers in an incomplete markets economy - Abreu, Rodrigo Soares de (2012)
This paper studies the behavior of fiscal multipliers in two different economic environments: complete markets and incomplete markets. Based on steady state analysis, output multipliers are found within a range between 0.49 and 0.66, when the markets are complete. Under incomplete markets, output multiplier was found in an interval between 0.75 and 0.94. These results indicates that the market structure, which reflects the degree of risk sharing and the intensity of the precautionary motive faced by individuals, plays a key role in determining the fiscal multipliers. In the second part of the paper, was performed an exercise to analyze the dynamic response of macroeconomic aggregates to an exogenous and unexpected rise in government spending financed by lump-sum taxes. In this case, impact output multipliers varies in a range between 0.64 and 0.68, under complete markets, and within 1.05 and 1.20 when markets are incomplete. The results found under incomplete markets are very close to that found on related literature which usually uses an econometric approach or calibrated/estimated New Keynesian models. These results shows that taking into account the deficiencies in the insurance mechanisms can be an interesting way to reconcile theoretical models with the results found on related current literature, without the need of ad-hoc assumptions relative to price stickness.